POST-WAR POLICY FOR STRUCTURAL MODERNIZATION OF THE UKRAINIAN ECONOMY: FOREIGN TRADE AND INSTITUTIONAL ASPECTS - Oleh V. Pustovoit; Tamara O. Ostashko; Oleksandr S. Bykonia; Volodymyr K. Olefir (Academy Review)
Since the 1960s, Western scholars have been collecting data on the dynamics and factors behind the postwar economic recovery of developing countries that have experienced military aggression, economic destruction, and human loss. Summarizing the collected data made it possible to propose the assumption that, in the context of a chronic lack of domestic financial resources, foreign (international) aid became the main factor in the accelerated post-war recovery of national economies. It was used more effectively in countries with better fiscal, monetary, and trade policies, as well as the rule of law. At the same time, it was assumed that businesses would independently find solutions regarding the areas of economic activity that should be developed to maximize their incomes. An increase in the level of economic activity in these areas would accelerate the growth of the national economy and shorten the period of its post-war recovery. Along with the works of Western scholars, the theoretical basis of this article draws on domestic studies, which demonstrate that, in Ukraine, international aid can play a key role in accelerating economic recovery – provided its use is guided not only by the needs of enterprises that have suffered destruction but also by a targeted state policy. This research focus is supported by the collected data, which show that, despite the war, the domestic economy still maintains the prerequisites for restoring the export-raw materials model of development. Historical experience has shown that this model is insufficient for ensuring high rates of economic growth and national reconstruction. To reduce the risks associated with restoring the export-raw materials model of development, the article proposes developing and implementing a state policy for the post-war structural modernization of the economy in Ukraine. Appropriate political measures should contribute to increasing the technological complexity of domestic commodity exports. An evidence base has been collected to justify the allocation of part of the state and international aid for the recovery and reconstruction of enterprises that, during the first five years after the war, will be able to produce export goods of increased technological complexity worth 11.765 billion USD (an average of 2.353 billion USD per year). To achieve such results, these enterprises should restore and increase by 54.9% the export of high-value (non-price, quality) competitive products; process approximately 27% of exported iron ore into final products; 8% of titanium ore; 25% of soybeans; and 5% of corn; and double the volume of organic product sales on foreign markets. If, in the post-war period, the export of goods begins to grow at the indicated volumes, and the export-to-import coverage ratio returns to the level of 2021 (i.e., to a value of 0.93, compared to 0.57 in 2023), then it can be expected that the forecasted average annual economic growth rate of Ukraine will increase from 3.5% to 6.5%. This will lead to a reduction in the economic recovery period from 8 to 5 years. Moreover, the recovery will occur at a qualitatively higher technological level compared to the economy that existed before 2021.